IMPORTANT VALUE OF COASTAL FOREST (INFLUENCE OF COASTAL DISTANCE TO SPECIES CONSERVATION AT AIPIRI MANOKWARI) - Slamet Arif Susanto; Simeon Abdi Putra; Heru Joko Budirianto (Biocelebes, 2019)
The conservation status of vegetation in coastal forest needs to be explored, because coastal forests are an area of development in the future. This study aims to compare coastal forest vegetation (A areas) with vegetation in habitats 600 meters from the shoreline (B areas) referring to the International Union for Conservation of Nature Resources (IUCN) conservation status. The method used the analysis of vegetation technique for determining the important value index (IVI), then each component of the IVI data is compared through the one way ANOVA test followed low significantly different test (LSD) at the P<0.05. The result showed that IVI components of vegetation in A areas belonging to the IUCN category were higher then vegetation in B areas. The vegetation in A areas categorized as IUCN was: Pongamia pinnata (L.) Pierre., Celtis philippensis Blanco., Intsia bijuga (Colebr.) Kuntze., Polyscias nodosa (Blume.) Seem., and Calophyllum inophyllum L., while in the types B areas in the IUCN category were dominated by Spathiostemon javensis Blume., Horsfieldia irya (Gaertn.) Warb., and Myristica fatua subsp. fatua. Vegetation of coastal forest needs to be prioritized as a conservation area, because species belonging to the IUCN category have high IVI.